Recovery and Resilience Facility funding in the Visegrád countries and its impact on Austria - Vasily Astrov; Robert Stehrer; Zuzana Zavarská (The Vienna Institute for International Economic Studies (wiiw), 2022)
To benefit from the newly established EU Recovery and Resilience Facility (RRF), the Visegrád countries - Czechia, Slovakia, Hungary, and Poland - have submitted their national recovery plans. The Czech and Slovak plans have already been approved by the EU, paving the way for the up-front disbursement of 13% of the requested funds. However, approval of the Hungarian and Polish plans is still pending. All plans mostly rely on EU grants, with only Poland requesting a small amount of EU loans. Although all plans meet the requirements of at least 37% to be spent on green transition and at least 20% on the digital economy, individual spending priorities vary by country. Czechia and Poland, which are strongly dependent on coal power generation, put a great emphasis on renewables and clean technologies (and digital skills in the case of Czechia), Hungary on health care and green transportation, and Slovakia on digital skills and health care. In the area of digital economy, all countries focus to a large extent on public services. Healthcare, education, transportation and utilities tend to be the main beneficiaries of RRF funding in the region, albeit with strong cross-country variation in the relative importance of individual sectors. The annual growth effect of total EU RRF spending is estimated to range, on average, between 0.6 pp in Czechia and 1.4 pp in Slovakia over the next five years. For Austria, the effect will be less pronounced (0.3 pp per year on average) because of the smaller size of its own RRF spending in relation to GDP. However, the Austrian economy will benefit from the positive demand spill-overs of RRF in the Visegrád countries due to its extensive production and trade links with the region. As the Visegrád countries gradually move towards the implementation phase of the RRF package, numerous policy implications for Austria arise. These include the encouragement of cross-border cooperation on projects (especially in the areas of green transition and health care), an active role in regional stakeholder engagement, and reinforcement of alignment with core EU goals and values.
Keywords: F0; H30; H50; H77; 330; Recovery and Resilience Facility; Visegrád countries; fiscal multiplier; input-output tables